2013
DOI: 10.1002/anie.201208684
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Chemistry of Red Phosphorus and Water under Near‐UV Irradiation

Abstract: A high‐pressure job: Under high‐pressure conditions, within a diamond anvil cell, irradiation of red phosphorus (see scheme, orange) and water was found to lead to a reaction that gives H2, PH3, H3PO2, H3PO4, and H3PO4 (H gray, O red, P orange). This reaction can be easily monitored using Raman spectroscopy and presents an interesting method for H2 generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 31 publications
(66 reference statements)
3
38
0
2
Order By: Relevance
“…Thef easibility of photolytic dehydrocoupling as specific reaction channel for functional phosphanes suggests that this transformation may also play ar ole in other photochemical processes (cf.t he photolytic high-pressure reaction of red phosphorus with water to give H 2 and phosphorus oxyacids [15] ), and we are currently studying possible applications for further types of phosphanes. Thef easibility of photolytic dehydrocoupling as specific reaction channel for functional phosphanes suggests that this transformation may also play ar ole in other photochemical processes (cf.t he photolytic high-pressure reaction of red phosphorus with water to give H 2 and phosphorus oxyacids [15] ), and we are currently studying possible applications for further types of phosphanes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thef easibility of photolytic dehydrocoupling as specific reaction channel for functional phosphanes suggests that this transformation may also play ar ole in other photochemical processes (cf.t he photolytic high-pressure reaction of red phosphorus with water to give H 2 and phosphorus oxyacids [15] ), and we are currently studying possible applications for further types of phosphanes. Thef easibility of photolytic dehydrocoupling as specific reaction channel for functional phosphanes suggests that this transformation may also play ar ole in other photochemical processes (cf.t he photolytic high-pressure reaction of red phosphorus with water to give H 2 and phosphorus oxyacids [15] ), and we are currently studying possible applications for further types of phosphanes.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, we have shown that functional phosphanes 1 and 1' ' undergo,u nlike PH 3 or P 2 H 4 ,s elective photochemically induced dehydrocoupling at room temperature.C omputational studies suggest that the reaction is initiated by formation of phosphane dimers whose photochemical excitation yields H 2 and the diphosphane.T his process can be implemented into ar eaction cycle which enables photocatalytic generation of H 2 on demand upon irradiation with UV light. Thef easibility of photolytic dehydrocoupling as specific reaction channel for functional phosphanes suggests that this transformation may also play ar ole in other photochemical processes (cf.t he photolytic high-pressure reaction of red phosphorus with water to give H 2 and phosphorus oxyacids [15] ), and we are currently studying possible applications for further types of phosphanes.…”
mentioning
confidence: 99%
“…This decomposition occurs very slowly over weeks and months but has been found to proceed rapidly under high pressures and UV radiation. [8] PH 3 and phosphoric acids severely affect the chemical stability of pyrotechnic formulations and compromise the safety of the munitions based thereon and the workers handling them. Pyrotechnic manufacturers have therefore been integrating absorbing pads based on active carbon into payload containers and have been designing PH 3 -venting mechanisms for payload casings.…”
mentioning
confidence: 99%
“…. [15] eine Rolle spielen kçnnte,u nd wir untersuchen derzeit mçgliche Anwendungen auf weitere Ty pen von Phosphanen.…”
Section: Angewandte Chemieunclassified